A hybrid fuzzy AHP-MABAC model: Application in the Serbian Army – The selection of the location for deep wading as a technique of crossing the river by tanks - Bozanic, Darko; Tešić, Duško; Milićević, Jovica (Decision Making: Applications in Management and Engineering, 2018)
In this paper is presented a hybrid model based on the fuzzified Analytical Hierarchical Process (AHP) method and the fuzzified Multi-Attributive Border Approximation Area Comparison (MABAC) method. The FAHP method is used for defining the weight coefficients of the criteria, while the FMABAC method is performed for the ranking of the alternatives. The fuzzification of the AHP method is carried out by defining a variable confidence interval for the values from the Saaty’s scale, which is derived from the comparison in pairs and the degree of certainty of the decision-makers in the comparison they make. The application of the hybrid model is shown on the example of the ranking of the locations for deep wading as a technique of crossing the river by the Serbian Army tank units. Through the paper are elaborated the criteria which condition such choice; also, the application of the method in a particular situation is demonstrated.